Encroachments as a problem for Sami reindeer husbandry - Rørholt, Anne Cathrine (Universitetet i Tromsø, 2009)
This thesis is about the loss of pastures as a problem for the Sami reindeer husbandry. The aim is to describe measures that may contribute to a new policy of dealing with the problem of the further loss of pastures perceived for the Sami reindeer areas. Whereas the Sami reindeer husbandry has managed to deal with the development so far, there are voices that claim: "Our land is taken bit by bit: one day it will be too much for us", and "this does not seem to be understood". The issue is studied from two different points of view, one shows how the reindeer herders view the problem today, the other shows the legal protection against loss of pastures in the past, present and proposed Norwegian legislation. The first study argues: To the reindeer herders, encroachments mean that they have to change their use of the areas. The problem is not the change of use. The problem arises when the alternatives for changing the use become too few. Complying with the problem is to improve the alternatives for changes of the reindeer herders' use of the pastures and to avoid unnecessary damage. This may be achieved by several means, "limited only by imagination", in the view of the informants used in the thesis, if only the reindeer herders may decide how. The second study argues: Whereas the Norwegian State at all times has recognized the right of the Sami reindeer herders to use the pastures, the legal protection against any loss of the pastures due to the development in society has been, and is weak. One of the objects of the Sami Right Committee, in their last report in 2007, was to propose legal measures to improve the protection against the losses of pastures in the Sami reindeer husbandry. This thesis argues that their proposal for a consultative institute seem to aim at refusing new losses of pastures, using the reindeer herders to front these refusals. This may prove to be a futile strategy, since new losses are likely to take place, and since there already is a need for improving the pasture conditions. In addition the ...